Cost Benefit Analysis of a Regional Arterial PPP Toll Road Project A Case Study of the Proposed R-1 Toll Road - Matanhire, Batsirai Brian (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
Road infrastructure is of vital importance. Roads facilitate the movement of people, goods, services and resources within an economy. Traditionally, public infrastructure such as roads has been provided using national budgetary resources. Over time participation of the private sector in the procurement and provision of road infrastructure has increased. Public authorities have been partnering with the private sector due to the limitation of capital to undertake required road projects. Public-Private Partnerships (PPPs) of various forms have been used extensively in road transportation projects as an alternative to state and local government procurement and provision of road infrastructure. The primary objective of this thesis is to undertake a holistic assessment of a proposed PPP toll road project in the Southern African country of Zimbabwe; using Cost-Benefit Analysis (CBA).

ÖZ: Karayolu altyapısı büyük önem taşımaktadır. Karayolları insanların, malların, hizmetlerin ve üretim faktörlerinin ekonomi içindeki hareketlerini kolaylaştırır. Geleneksel olarak, karayolları gibi açık altyapılar ulusal bütçe kaynakları kullanılarak sağlanmaktaydı. Zaman içinde özel sektörün karayolları alımı ve tedariğine katılımı, altyapıyı arttırdı. Yetkili Kamu makamları gerekli yol projelerini üstlenecek sermayenin sınırlı olmasından dolayı özel sektörle ortaklık yapmaktadır. Eyalet ve yerel yönetimin karayolu alımı ve tedariğine alternatif olarak, Kamu - Özel Ortaklıkları (PPPs), çeşitli biçimlerde, karayolu ulaştırma projelerinin yapımında sıklıkla kullanılmıştır. Bu tezin temel amacı, Fayda-Maliyet Analizini (CBA) kullanarak Günay Afrika ülkesi Zimbabve’de, Kamu - özel ortaklığında (PPP) önerilen ücretli yol projesinin bütünsel değerlendirmesini yapmaktır.
Master of Science in Banking and Finance. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2019. Supervisor: Prof. Dr. Glenn Paul Jenkins.
Keywords: Banking and Finance; Road projects--Evaluation; Infrastructure; Toll Road; Public-Private Partnership; Cost Benefit Analysis; Zimbabwe